PELATIHAN MENULIS PUISI DENGAN MEDIA GAMBAR PADA SISWA KELAS VII SMP NEGERI KOTA BARU KEFAMENANU - Joni Soleman Nalenan (LPPM Universitas Timor, 2020)
The dedication entitled “The Training of Poetry Writing using picture to Grade Seven of SMPN Kota Baru Kefamenanu”. This activity aimed to provide knowledge and explaination to students in SMPN Kota Baru Kefamenanu about the procedure to create a poetry using picture; improve students' creativity in writing poetry using picture; and motivate students regarding the importance of the writing, and develop literature like poetry. The targets of this dedication activity were 30 students in SMPN Kota Baru Kefamenanu. This training was implemented through two methods, there are communicative method and action method. Communicative method was used to explain the topics like essence of poetry, and how to create poetry. Action method was used to practice writing a poetry based on observation results of the provided picture. The anthusiasm from the participants, the supports from the head masters and co-teachers, and the financial support from LPPM are helpful in accomplishing this dedication. As a result, the ability of students of grade VII in SMPN Kota Baru Kefamenanu in creating a poetry especialy using picture is at medium category with average score 67.